The other one. Series 1 [videorecording (DVD)] - Walsh, Holly (Acorn, 2020)
When her husband dies at his surprise party, Tess gets a bigger shock when she learns he had a secret family. Now she and her uptight daughter, Cathy, must get to know playful Marilyn and her daughter, Cat.